If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2y = 62 Solving 2x + 2y = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 2x + 2y + -2y = 62 + -2y Combine like terms: 2y + -2y = 0 2x + 0 = 62 + -2y 2x = 62 + -2y Divide each side by '2'. x = 31 + -1y Simplifying x = 31 + -1y
| -210x+6y=330 | | -19a-12+4a=-57 | | -8x^2+14x=12 | | 3n+7-8n=34-11n+21 | | 3(3x+1)=-6 | | 10-5-3x-2x=0 | | -8x^2+14=-12 | | 18x^3-15x^2-7x= | | 2a^2-52-8a=32+a^2-3a | | -3x+2y-(7+x)+(x+7)= | | W=8g+700 | | 3(4+x)=-8(6-x) | | -4a+3-6a-8=15 | | -94=5(2m+2)-2m | | 9(y-1)-(y-5)=10 | | 2Y+4y-8y=36 | | 4p+yr=r-9f | | Y=8g+700 | | 6+4y+10=18 | | 2(4a+3)(a+1)=21 | | 2r-6-7r-9= | | 5(2p-4(p+5))=1 | | 4(3x+2)=200 | | 20x^3-11x^2-9x= | | 4(x+3)-4=8x+104x | | 6+3(b+4)=5b+(b-9) | | 3(1)-5y=0 | | x+8-3=4+3-5 | | 13+5b+7b=5b-7+2b | | (4x+4)(2x+9)= | | 81x^3-36x=0 | | 36x=360 |